A METHOD AND ALGORITHM FOR SIMULATING THE INFLUENCE OF THERMALLY COUPLED SURFACE RADIATION IN CASTING PROCESSES (2015)
A method for simulating the influence of thermally coupled surface radiation on a solid body, which solid body has at least one surface capable of being exposed to radiation, by calculating the radiative exchange between grey, diffuse surfaces, characterized in that the surface or surfaces to be exposed to radiation is/are subdivided adaptively, hierarchically into radiation tiles of the same or virtually the same radiation intensity, and the surface temperature resulting from irradiation is achieved by means of a hierarchical view factor method, which view factor method includes the evaluation of a solid angle integral using a primary solid angle subdivision, which primary solid angle subdivision has a homogeneous view factor discretization, wherein each solid angle subdivision is adaptively and hierarchically discretized into its partial areas by spherical projection and wherein the total of all partial amounts of that solid angle integral can be determined by means of ray tracing.